Comparison between Hand Suture and Carter-Thomason Needle Closure of Port Sites in Laparoscopy - shetty, abijit; Adiyat, Kishore Thekke (Urology Journal, 2014)
Purpose: To compare between hand closure and Carter-Thomason technique with respect to following parameters, time taken for port site closure, wound infection, wound dehiscence, seroma formation, port site herniation, and ascitic fluid leak. Materials and Methods: In this study, 200 cases who underwent laparoscopic donor nephrectomy were selected and divided into two groups based on closure technique. First 100 cases underwent port closure by the standard hand closure technique and next 100 cases by Carter-Thomson needle technique. Subjects included in this group are healthy individuals with no co morbid illness. This might help to reduce the bias of complications arising from other than technical issue. Results: In our study Carter-Thomason serves as a better mode of port site closure with respect to time reduced, wound and bowel related complications compared to hand closure technique. Conclusion: In this study closure of trocar site is better with the Carter-Thomason method when compared to hand closure technique.